In Vitro Assessment of the Interaction Potential of Ocimum basilicum (L.) Extracts on CYP2B6, 3A4, and Rifampicin Metabolism - Kumar, Saneesh; Bouic, Patrick J.; Rosenkranz, Bernd (Frontiers in Pharmacology, 2020)
Ocimum basilicum L. or basilicum is a common culinary herb, used as a traditional medicine for various medical conditions including HIV/AIDS and tuberculosis, in Africa. The objective of this study was to evaluate the effect of methanol, ethanol, aqueous and ethyl acetate extracts of the dried leaves and inflorescence of O. basilicum, on the activity of cytochrome P450 enzymes (CYPs) CYP2B6 and 3A4, as well as esterase-mediated metabolism of rifampicin to 25-O-desacetyl rifampicin (25ODESRIF). Human liver microsomes (HLM) were used to evaluate inhibition and CYP2B6/3A4 mRNA expression HepG2 assays were used to measure induction. Furthermore, the phytoconstituents likely involved in causing the observed effect were analyzed using biochemical tests and LC-MS. The aqueous and methanolic extracts showed reversible and time-dependent inhibition (TDI) of CYP2B6 with TDI-IC50s 33.35 μg/mL (IC50 shift-fold >1.5) and 4.93 μg/mL (IC50 shift-fold >7) respectively, while the methanolic and ethanolic extracts inhibited 25ODESRIF formation (IC50s 31 μg/mL, 8.94 μg/mL). In HepG2 assays, the methanolic and ethanolic extracts moderately induced CYP2B6, 3A4 mRNA with 38%-, 28%-fold shift, and 22%-, 44%-fold shift respectively. LC-MS full scans identified phenols rosmarinic acid (m/z 359 [M-H]-, approximately 2298 mg/L in aqueous extract) and caftaric acid along with flavones salvigenin (m/z 329 [M+H]+, approximately 1855 mg/L in ethanolic extract), eupatorin (m/z 345 [M+H]+, 668.772 mg/L in ethanolic extract), rutin (m/z 609 [M-H]-) and isoquercetin (m/z 463 [M-H]-) and other compounds - linalool (m/z 153 [M-H]-), hydroxyjasmonic acid (m/z 225 [M-H]-), eucommiol (m/z 187 [M-H]-) and trihydroxy octadecenoic acid (m/z 329 [M-H]-, 530 mg/L in ethanolic extract). The putative gastrointestinal tract (GIT) concentration for all extracts was calculated as 2400 μg/ml and hepatic circulation concentrations were estimated at 805.68 μg/ml for the aqueous extract, and 226.56 μg/ml for methanolic extract. Based on the putative GIT concentration, estimated hepatic circulation concentration [I] and inhibition constant Ki, the predicted percentile of inhibition in vivo was highest for the aqueous extract on CYP2B6 (96.7%). The observations indicated that O. basilicum extracts may have the potential to cause clinically relevant herb-drug interactions (HDI) with CYP2B6 and rifampicin metabolism in vivo, if sufficient hepatic concentrations are reached in humans.